Studi Pembelian Antibiotik Tanpa Resep di Apotek Kita, Kota Jambi - pratama, septa (Sahabat Publikasi Kuu, 2022)
Background: Antibiotics are prescription drugs that must be obtained from a doctor. However, because it is now available without a doctor's prescription, the potential for resistance is even greater. The purpose of this study is to determine the pattern of antibiotic purchases at Our Pharmacy without a doctor's prescription. Methods: This is a descriptive observational study to see how to buy antibiotics at our pharmacies without a doctor's prescription. The population of this study included all customers who came to our pharmacy to buy drugs, and the sample included customers who purchased antibiotics without a prescription. The samples were collected using the incidental sampling technique. The results: showed that the sex who purchased the most antibiotics was male (61.05%). The majority of the age group is over 40 years old (52.13%). According to the reasons for purchasing antibiotics, the majority of patients (18.75%) purchased antibiotics because they had coughs and colds, while amoxycillin was the most commonly purchased antibiotic (43.75%). Conclusion: Based on the results, it is possible to conclude that free antibiotic purchases continue to occur in our pharmacies, with the majority of patients being male. Those over the age of 40 make up the majority of the age group. Antibiotics are typically purchased without a doctor's prescription due to complaints of cough and cold with the main antibiotic, amoxycillin.